A Study on Seismic Isolation of Shield Tunnel Using Quasi-Static Finite Element Method - Can Li; Weizhong Chen; Wusheng Zhao; Takeyasu Suzuki; Yoshihiro Shishikura (Shock and Vibration)
Using a quasi-static method based on an axisymmetric finite element model for seismic response analysis of seismically isolated tunnels, the seismic isolation effect of the isolation layer is studied, and the seismic isolation mechanism of the isolation layer is clarified. The results show that, along the longitudinal direction of the tunnel, the seismic isolation effect is mainly affected by the shear modulus of the isolation material. The smaller the shear modulus is, the more evident the seismic isolation effect is. This is due to the tunnel being isolated from deformation of its peripheral ground through shear deformation of the isolation layer. However, along the transverse direction of the tunnel, the seismic isolation effect is mainly affected by the shear modulus and Poisson’s ratio of the isolation material. When Poisson’s ratio is close to 0.5, a seismic isolation effect is not evident because the tunnel cannot be isolated from deformation of its peripheral ground through compression deformation of the isolation layer. Finally, a seismic isolation system comprising a shield tunnel in which flexible segments are arranged at both ends of an isolation layer is proposed, and it is proved that the seismic isolation system has significant seismic isolation effects both on the longitudinal direction and on the transverse direction.